CLINICAL AND IMMUNOLOGICAL EFFICACY OF INOSINE PRANOBEX FOR ACUTE RESPIRATORY INFECTIONS IN CHILDREN WITH ATOPIC ASTHMA - V.A. Bulgakova; I.I. Balabolkin; M.S. Sedova; S.G. Shmakova; I.V. Zubkova; E.L. Korol'kova (Педиатрическая фармакология)
The prevalence rate of atopic asthma in children remains high. One of the reasons for lack of control over asthma symptoms is repeated infection. The article describes results from the study of immunomodulating medication inosine pranobex used in treatment of acute respiratory infections in children with atopic asthma. The results obtained prove the efficacy and safety of this medication. The use of this immunomodifier with antiviral activity during the period of acute respiratory infection in children with atopic asthma contributes to shortening of intoxication and catarrhal signs duration, elimination of viral agents. Key words: asthma, acute respiratory infections, immunomodifiers, inosine pranobex, children. (Pediatric Pharmacology. – 2010; 7(3):98-105)